Locomotive On-board Data Dump System Based on Automatic Task Model - DENG Zhifeng; WANG Yu; YU Zhihao (Kongzhi Yu Xinxi Jishu)
In order to meet the requirements of safety, reliability, efficiency and intelligence of locomotive on-board data dump, an intelligent dump system with video clipping function and a set of file priority was designed, and its functions including on-board data acquisition, task management, data synchronization, dump and ground system were introduced in detail. Compared with the traditional dump model, the system adopts automatic task model, and can configure the data dump strategy flexibly. As a result, the whole dump process needs no manual intervention. Data dynamic encryption, breakpoint continuation and packet retransmission based on UDP were designed to make data dumps safer and more efficient. Field verification was carried out by Shenhua locomotive. The results show that all the functions have met the needs of the field and the system is suitable for large scale application.